Genetics of stroke in a UK African ancestry case-control study: South London Ethnicity and Stroke Study. (April 2017) - Traylor, Matthew; Rutten-Jacobs, Loes; Curtis, Charles; Patel, Hamel; Breen, Gerome; Newhouse, Stephen; Lewis, Cathryn M.; Markus, Hugh S.
Abstract : Objective: Despite epidemiologic data showing an increased stroke incidence in African ancestry populations, genetic studies in this group have so far been limited, and there has been little characterization of the genetic contribution to stroke liability in this population, particularly for stroke subtypes. Methods: We evaluated the evidence that genetic factors contribute to stroke and stroke subtypes in a population of 917 African and African Caribbean stroke cases and 868 matched controls from London, United Kingdom. We (1) estimated the heritability of stroke in this population using genomic-relatedness matrix-restricted maximum likelihood approaches, (2) assessed loci associated with stroke in Europeans in our population, and (3) evaluated the influence of genetic factors underlying cardiovascular risk factors on stroke using polygenic risk scoring. Results: Our results indicate a substantial genetic contribution to stroke risk in African ancestry populations (h 2 = 0.35 [SE = 0.19], p = 0.043). Polygenic risk scores indicate that cardiovascular risk scores contribute to the genetic liability (odds ratio [OR] 1.09 [95% confidence interval (CI) 1.01–1.17], p = 0.029) and point to a strong influence of type 2 diabetes in large vessel stroke (OR 1.62 [95% CI 1.19–2.22], p = 0.0024). Single nucleotide polymorphisms associated with ischemic stroke in Europeans shared direction of effect in SLESS ( p = 0.031), suggesting that disease mechanisms are shared across ancestries. Conclusions: Stroke in African ancestry populations is highly heritable and influenced by genetic determinants underlying cardiovascular risk factors. In addition, stroke loci identified in Europeans share direction of effect in African populations. Future genome-wide association studies must focus on incorporating African ancestry individuals.